Factors that contribute to the pest and disease attack in oil palm at Kluang, Johor and Jasin, Melaka / Muhammad Faris Muhamad Eshammuddin - Muhamad Eshammuddin, Muhammad Faris (Faculty of Plantation and Agrotechnology, 2018)
Malaysia is one of the largest producer of palm oil globally and have export the palm oil to other country such as China, Pakistan and European country. Hence, pest and disease have become one of major problem because of yield loss and growth disruption. There various pest and disease that cause disruption in many stage from seedling until matured in oil palm cultivation such as rhinoceros beetle, rat and basal stem rot. If uncontrollable, it can cause total loss on the plantation and reduce the fresh fruit bunch yield. Therefore, this study is conducted to know what is the factor that can contribute toward the pest and disease attack, the most factors that contributed and the relationship toward it. The data was collected by distributing questionnaire at the IOI plantation in Johor and Melaka area. There are four factors that will be observed in this study which are estate field management, neighbour estate field management and condition, surrounding environment and pest and disease history. The questionnaire was distributed to the staff management starting from field supervisor until manager with total of 53 respondents. From the result, it shows that the surrounding environment and pest and disease history in the area is the factors that contribute towards the pest and disease attack. Data also shows that surrounding environment is the most strong factor among other 4 factor that contribute toward pest and disease attack.